A novel wideband circularly-polarized microstrip antenna array based on DGS for wireless power transmission - Fatima Ouberri; Abdelali Tajmouati; Noha Chahboun; Larbi El Abdellaoui; Mohamed Latrach (Universitas Ahmad Dahlan, 2022)
The requirement for applications operating at a variety of frequencies in a unified wireless device has greatly enhanced in recent years. For this purpose, multi-functional wireless components are essential. This paper presents a new design of a wideband circularly-polarized microstrip antenna array with defected ground structure (DGS). A previous design was introduced which cover the C-band at 5.8 GHz and operates in the industrial scientific medical (ISM) band for wireless communication applications. The proposed antenna has excellent performances which include good input impedance matching with a fed of the circular polarization at 5.8 GHz. The proposed design is validated and optimized by adding a new design of defected ground structure. This aperture geometry enables the antenna to operate in a wideband. The obtained results show that the modified antenna has a good performance in terms of return loss, bandwidth, gain and radiation pattern and demonstrate that the proposed antenna offers a good solution for multi-standard wireless communication applications